Kegagalan Peraturan Penanganan Covid-19 di Indonesia - Fikri Hadi; Farina Gandryani (Jurnal Konstitusi, 2022)
COVID-19's occurrence in Indonesia requires the use of a variety of legal instruments related to COVID-19 in Indonesia. In practice, the existence of various legislative laws creates new legal concerns, such as failure to implement in connection to the original handling of COVID-19. Both Lon Fuller's concept of legal failure and Emergency Constitutional Law can be used to explain this failure. According to this article, failure to implement COVID-19 handling manifests itself in a variety of ways: First, laws and regulations have yet to incorporate the concept of an outbreak as a disaster. Second, the government neglected to adopt legislative rules through the provisions of the Health Authenticity Acts. Third, the failure to establish consistent and evolving regulations was not caused by the controlled medications or the regulations in place. According to this article, the regulation failed because the government did not declare a state of emergency prior to its enactment.